This Study Investigates How Role Playing Combined with Musical Drama Improves Fifth-Grade Students’ Indonesian Speaking Skills and Learning Motivation in Sintuk Toboh Gadang Elementary Schools - Fitri Yani A.R; Weni Yulastri; Hafiz Hidayat (FKIP - Universitas Riau, 2026)
Low speaking skills and learning motivation among students remain a challenge in elementary education, as speaking is a key productive language skill and motivation affects students’ willingness to practice. This study aimed to examine the effectiveness of the Role-Playing method assisted by musical drama in improving speaking skills and learning motivation of fifth-grade students at 07 Sintuk Toboh Gadang and 10 Sintuk Toboh Gadang elementary schools. A quasi-experimental design with non-randomized classes was employed. Oral tests measured speaking skills, while questionnaires assessed learning motivation. Normality and homogeneity tests confirmed the suitability of the data for analysis. The experimental class showed an increase in mean scores from 48 in the pretest to 67 in the posttest. T-test analysis indicated a significant difference between the experimental and control classes, with t-count 7.795 exceeding t-table 2.023. The learning motivation questionnaire was valid and reliable, with r-count exceeding r-table and Cronbach’s Alpha of 0.884. The findings indicate that the Role-Playing method assisted by musical drama effectively enhances both speaking skills and learning motivation of fifth-grade students.